Determinants of Public Education Expenditures: Analysis for Junior and Senior Secondary Education in Nigeria - Awulor-Hephzibah, B. N. (International Journal of Educational Management, 2025)
T he aim of the paper is to analyze factors influencing spending behaviors on education. The special focus is given to degree of decentralization tasks related to education. It is believed that local chairmen/governors do not actively influence salaries of the teachers. The revenues or more generally differences in financial statement of local units do not importantly explain the variation in this task. States change the level of salaries according to federal regulations and increase them accordingly. On the other hand they do not decide to change number of teachers, even in case of lowering number of pupils in schools and also deteriorating financial statement due to economic crisis. So in case of more centralized and less flexible task we can observe incremental budget behaviors. The spending on school maintenance and school supplies are more influenced by revenues of local government and would be modified more dramatically, when they are changed The budget policy in case of more decentralized task seems to be more elastic and more differentiated among government. On one hand this is the result of decentralization and could be visible as representation of real local needs. On the other, ii could impose problems of politicians influence on budget policy. In year of election these expenditures are higher than in other years. Base on qualitative study, one can observe also, that in time of crisis "fixed" spending onsalaries pushed expenditures for maintenance and school supplies out, it can result important problem in vertical equity of education